Exploring Advanced Sandwiched Arrays by Vertical Graphene and N‐Doped Carbon for Enhanced Sodium Storage. Issue 3 (12th October 2016) - Xie, Dong; Xia, Xinhui; Zhong, Yu; Wang, Yadong; Wang, Donghuang; Wang, Xiuli; Tu, Jiangping
Abstract : Smart hybridization of active materials into tailored electrode structure is highly important for developing advanced electrochemical energy storage devices. With the help of sandwiched design, herein a powerful strategy is developed to fabricate three‐layer sandwiched composite core/shell arrays via combined hydrothermal and polymerization approaches. In such a unique architecture, wrinkled MoSe2 nanosheets are sandwiched by vertical graphene (VG) core and N‐doped carbon (N‐C) shell forming sandwiched core/shell arrays. Interesting advantages including high electrical conductivity, strong mechanical stability, and large porosity are combined in the self‐supported VG/MoSe2 /N‐C sandwiched arrays. As a preliminary test, the sodium ion storage properties of VG/MoSe2 /N‐C sandwiched arrays are characterized and demonstrated with high capacity (540 mA h g −1 ), enhanced high rate capability, and long‐term cycling stability (298 mA h g −1 at 2.0 A g −1 after 1000 cycles). The sandwiched core/shell structure plays positive roles in the enhancement of electrochemical performances due to dual conductive carbon networks, good volume accommodation, and highly porous structure with fast ion diffusion. The directional electrode design protocol provides a general method for synthesis of high‐performance ternary core/shell electrodes. Abstract : A powerful strategy to fabricate three‐layer sandwiched vertical graphene/MoSe2 /N‐doped carbon (VG/MoSe2 /N‐C) core/shell arrays via combined hydrothermal and polymerization approaches is developed. The designed VG/MoSe2 /N‐C composite exhibits a noticeable enhancement of sodium storage.